COVID‐19 patients in intensive care develop predominantly oliguric acute kidney injury. Issue 3 (28th November 2020) - Luther, Tomas; Bülow‐Anderberg, Sara; Larsson, Anders; Rubertsson, Sten; Lipcsey, Miklos; Frithiof, Robert; Hultström, Michael
Abstract : Background: Acute kidney injury (AKI) is a syndrome of reduced glomerular filtration rate and/or reduced urine flow associated with mortality in corona virus disease 2019 (COVID‐19). AKI is often associated with renal tissue damage, which may lead to chronic kidney disease. Biomarkers of tissue damage may identify patients of particular risk. Methods: In a prospective observational study of 57 patients admitted to intensive care, AKI incidence and characteristics was evaluated according to KDIGO criteria and related to days after admission. Urinary albumin, Neutrophil Gelatinase‐Associated Lipocalin (NGAL), Kidney Injury Molecule 1 (KIM‐1) and Plasma Tissue Inhibitor of MetalloProteinase 2 (TIMP‐2) were analysed in 52 patients at admission. The majority (n = 51, 89%) of patients developed AKI, and 27 (47%) patients had predominantly oliguric AKI where oliguria was more severe than plasma Creatinine increase. Severe oliguria within first 2 days after admission was common (n = 37, 65%), whereas stage 2 and 3 AKI due to Creatinine occurred later than day 2 in 67% (12/18) of cases. Renal replacement therapy was started in 9 (16%) patients, and 30‐day mortality was 28%. Urinary biomarkers were increased in a majority of patients, but did not robustly predict KDIGO stage. Most patients had microalbuminuria, and severe albuminuria (albumin Creatinine ratio > 30 mg/mmol) was found in n = 9 (17%) patients. Conclusions: A majority of patients with COVID‐19 admitted to the ICU develop AKI. The functional deficit is often low urinary volume, and initial levels of biomarkers are generally increased without clear relation to final AKI stage.